A Decade of Dugong (Dugong dugon) Strandingsin Indonesia: Frequency and Response Efforts (2016–2025) - Saraswati, Suprabadevi Ayumayasari; Putra, I Putu Gede Eka Handrayana; Kartika, I Wayan Darya; DZulfikar, Rizka; Saputra, Dewa Gde Tri Bodhi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Indonesian waters constitute a crucial habitat for the dugong (Dugong dugon), a herbivorous marine mammal currently classified as vulnerable. Despite being legally protected, its existence remains threatened by anthropogenic activities and stranding phenomena. This study aims to analyze the temporal frequency of dugong stranding events in Indonesia and the effectiveness of their technical response schemes. The method employed is a descriptive approach with quantitative and qualitative analyses utilizing verified secondary data from the 2016–2025 period. The results show that a total of 54 stranding events occurred fluctuatingly, with an average of 5–6 cases per year. The highest spike occurred in 2021 with 12 events, while the lowest was in 2020 with 1 event. The monthly stranding pattern is dynamic, reaching its highest peak in February, whereas the monsoon-based analysis demonstrates an even distribution of approximately 24%–26% per monsoon. This finding indicates that the risk of stranding remains persistent throughout the year. Out of the total cases, the majority of dugongs were found dead (90.74%), while the remaining (9.26%) were found alive. Qualitatively, the systematic handling procedures in the field have been structured into four main phases that separate actions based on the animal's condition code. Response for the live code (Code 1) focuses on first aid and release, whereas the dead code (Code 2–5) is prioritized for medical investigation (forensic necropsy) and burial.